2012
DOI: 10.1007/s12105-012-0368-1
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus in Non-Oropharyngeal Head and Neck Cancers: A Systematic Literature Review

Abstract: Perhaps one of the most important developments in head and neck oncology of the past decade is the demonstration that patients with human papillomavirus (HPV)-mediated oropharyngeal cancers have significantly improved outcomes, compared to HPV-negative counterpart patients. This has become the basis for clinical trials investigating the impact on ''treatment deintensification'' for patients with HPV-mediated oropharyngeal cancers. Unfortunately, the significance of HPV in non-oropharyngeal head and neck cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
218
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(235 citation statements)
references
References 114 publications
5
218
1
3
Order By: Relevance
“…However, high rates of HPV infection have rarely been demonstrated in the oral cavity and are an unlikely explanation for the increased incidence and impact the survival rate of younger patients (Isayeva et al, 2012). Goot-Heah et al (2012) indicated a low viral load of high-risk HPV in Malaysian OSCC by analysing virus PCR product from saliva samples, suggesting the prevalence of HPV infection may not be important in Malaysian OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…However, high rates of HPV infection have rarely been demonstrated in the oral cavity and are an unlikely explanation for the increased incidence and impact the survival rate of younger patients (Isayeva et al, 2012). Goot-Heah et al (2012) indicated a low viral load of high-risk HPV in Malaysian OSCC by analysing virus PCR product from saliva samples, suggesting the prevalence of HPV infection may not be important in Malaysian OSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last three decades, the high-risk HPV genotypes (hrHPV) have been confirmed as the major etiologic factor of the subset of oropharyngeal SCC, dominating in the western part of the world [14,15]. The significance of hrHPV infection in the development of tumours in oral cavity, hypopharynx and larynx needs to be additionally elucidated [1,2,[16][17][18]. Controversial data on hrHPV DNA prevalence in hypopharyngeal and laryngeal SCC has been published; prevalence varied considerably, from 5 to 60% [4,19,20].…”
Section: Etiopathogenesis Of Conventional Squamous Cell Carcinoma Sumentioning
confidence: 99%
“…A specific role was hypothesized way back in 1983, but till date, a definite consensus still awaits the light of the day [6][7][8]. The healthy adult population has showed prevalence for any HPV type of 2-8 % in OCSCC [9][10][11][12][13][14] with a higher preponderance for male sex worldwide [11][12][13]15] whereas previous Indian studies have reported a wide variation in HPV positivity prevalence from northeastern, eastern, and southern different regions of the country [16][17][18][19][20]. Further high-risk sexual behavior including oral genital sex and multiple sexual partners has been found to be associated with HPV transmission [12,21,22].…”
Section: Introductionmentioning
confidence: 99%